DCZ0415, a small‐molecule inhibitor targeting TRIP13, inhibits EMT and metastasis via inactivation of the FGFR4/STAT3 axis and the Wnt/β‐catenin pathway in colorectal cancer. Issue 8 (7th March 2022) - Agarwal, Sumit; Afaq, Farrukh; Bajpai, Prachi; Kim, Hyung‐Gyoon; Elkholy, Amr; Behring, Michael; Chandrashekar, Darshan Shimoga; Diffalha, Sameer Al; Khushman, Moh'd; Sugandha, Shajan P.; Varambally, Sooryanarayana; Manne, Upender
Abstract : Thyroid receptor‐interacting protein 13 (TRIP13), a protein of the AAA‐ATPase family, is upregulated in various human cancers, including colorectal cancer (CRC). This study focused on the inhibition of TRIP13‐induced CRC progression and signalling by DCZ0415, a small molecule targeting TRIP13. It demonstrated potent antitumour activity in TRIP13‐deregulated cancer cell lines, regardless of their p53, KRAS, BRAF, epidermal growth factor receptor or microsatellite instability status. The treatment of CRC cells with DCZ0415 resulted in decreased cell proliferation, induced cell cycle arrest in the G2‐M phase and increased apoptosis. DCZ0415 diminished xenograft tumour growth and metastasis of CRC in immunocompromised mice. DCZ0415 reduced expression of fibroblast growth factor receptor 4 (FGFR4), signal transducer and activator of transcription 3 (STAT3), and proteins associated with the epithelial‐mesenchymal transition and nuclear factor kappa B (NF‐κB) pathways in cells and xenografts exhibiting high expression of TRIP13. Additionally, DCZ0415 decreased cyclin D1, β‐catenin and T‐cell factor 1, leading to the inactivation of the Wnt/β‐catenin pathway. In a syngeneic CRC model, DCZ0415 treatment induced an immune response by decreasing PD1 and CTLA4 levels and increasing granzyme B, perforin and interferon gamma. In sum, DCZ04145 inhibits the TRIP13–FGFR4–STAT3 axis, inactivates NF‐κB and Wnt/β‐catenin signalling, activates antitumour immune response and reduces the progression and metastasis of CRC. This study provides a rationale to evaluate DCZ0415 clinically for the treatment of a subset of CRCs that exhibit dysregulated TRIP13 and FGFR4. Abstract : TRIP13 is upregulated in patients with colorectal cancer (CRC). Here we investigated the effect of the TRIP13‐specific inhibitor DCZ0415 and observed that it blocked the TRIP13/fibroblast growth factor receptor 4 (FGFR4)/signal transducer and activator of transcription 3 axis, epithelial–mesenchymal transition, nuclear factor kappa B and Wnt/β‐catenin signalling pathways. Thus, DCZ0415 may have a potential role in treating a subset of patients with CRC that exhibit dysregulated TRIP13 and FGFR4 expression.